PENGARUH KUALITAS PELAYANAN, PRODUK, DAN DESAIN PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI INTERVENING KEPUASANl - Suselo, Antonius (Prodi Magister Manajemen FE-UST, 2018)
This study aims: (1) To determine the effect of quality, product and product design on customersatisfaction; (2) To know affect the quality of service, product, and product design to customer loyalty;and (3) To know the influence of consumer to customer loyalty. Population in this research is allconsumer of Modena area of Yogyakarta branch with sample 100 people. The technique uses data usingquestionnaires. The analysis is a multiple regression analysis and path analysis. Based on the researchresult, it can be concluded that: (1) There is a significant positive effect of service quality, productquality, and product design on satisfaction of Modena product in Yogyakarta branch area (2) there issignificant positive influence of service quality, product quality, product design and satisfactioncustomer to customer loyalty on Modena product in branch area of Yogyakarta. (3) There is a significantpositive effect to consumers on customer loyalty of Modena product in Yogyakarta branch area.Keywords: service quality, product quality, product design, loyalty customers, customer satisfaction.